THE USE OF DIGITAL EDUCATIONAL RESOURCES IN TEACHING THE RUSSIAN LANGUAGE AT HIGHER EDUCATION INSTITUTIONS OF ARTS AND CULTURE: A SOCIO-ECONOMIC PERSPECTIVE (Eureka Journal of Humanities and Social Research, 2026)
The article examines methodological and socio-economic aspects of using digital educational resources in teaching Russian at universities of arts and culture in Uzbekistan. The impact of educational digitalization on the development of linguistic and communicative competencies of students of creative specialties, as well as on human capital development, is analyzed. Special attention is paid to the didactic potential of digital technologies, their role in increasing students’ motivation and developing professionally oriented speech activity. The relevance of combining digital and traditional teaching methods in modern socio-economic conditions is substantiated.
Keywords: Digital educational resources, Russian language, higher education, teaching methodology, digitalization of education, socio-economic aspect, human capital.